Cellular Network Planning Toward 2021 Case Study: Bukit Raya District Pekanbaru - Rahayu, Yusnita; Sofyan Lubis, Ahmad (International Journal of Electrical, Energy and Power System Engineering, 2018)
Due to the advancement of telecommunication platform, users are now demanding high performance application. Propagation models play a vital role in the characterization and design of wireless and mobile communications networks. However, if they are utilized in a different environment than the one they were formulated for, propagation path-loss models may produce unacceptable deviation in predictions. Nowadays every mobile service provider continues to build a telecommunications tower with little regard for its impact on the area function. This paper presents the cellular network planning in the district of Bukit Raya, Pekanbaru. From the field survey, there are found sixty-two (62) cell sites. This number is extremely large compared to the calculated one. From the theory, only twenty-five (25) cell sites are required. Thus, it was found inappropriate deployment cell sites.